An Alternative Perspective to “the Owenite Movement” Window to Sustainable Cities: “Neighbourhood Cooperatives” - Kanli, I. Bakir (European Journal of Sustainable Development, 2016)
The struggle for sustaining existence and environment of humans is as old as humanity. Capitalism has accelerated problems relating to sustainability. Many scholars have endeavoured to address these problems by purposing an alternative social order. Robert Owen is one of these scholars. He shares that the clues for reaching sustainable communities could be achieved by advocating a cooperative-oriented life style. Even though his idea of villages of cooperation became an intellectual phenomenon this theoretical phenomenon of the Owenite Movement, proved a practical failure due to several inaccuracies. In this paper, developments of the cooperative system concepts, the Owen’s point of view and his implementations are analysed. Through the analyses the new term of “Neighbourhood Cooperatives”, which may play a key role in fulfilling the basic services of local community, is proposed. The term is considered as a strategic tool embracing entirely the components of sustainability. These components include social, economic, environmental and governance which are also seen as a building blocks leading to sustainable cities. The paper also deals with the scope of neighbourhood cooperatives, its functions and services, and their positions at a management level. And in the final section particular inferences will be made regarding possible benefits such as social, cultural, economic and governance. Keywords: Sustainability, Neighbourhood, Cooperative, Owenite movement, Neighbourhood Cooperatives